If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5x + 4 + 9 = 4x + 4 + 6x Reorder the terms: 4 + 9 + 6x + 5x = 4x + 4 + 6x Combine like terms: 4 + 9 = 13 13 + 6x + 5x = 4x + 4 + 6x Combine like terms: 6x + 5x = 11x 13 + 11x = 4x + 4 + 6x Reorder the terms: 13 + 11x = 4 + 4x + 6x Combine like terms: 4x + 6x = 10x 13 + 11x = 4 + 10x Solving 13 + 11x = 4 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 13 + 11x + -10x = 4 + 10x + -10x Combine like terms: 11x + -10x = 1x 13 + 1x = 4 + 10x + -10x Combine like terms: 10x + -10x = 0 13 + 1x = 4 + 0 13 + 1x = 4 Add '-13' to each side of the equation. 13 + -13 + 1x = 4 + -13 Combine like terms: 13 + -13 = 0 0 + 1x = 4 + -13 1x = 4 + -13 Combine like terms: 4 + -13 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| .5x+13=9 | | X^2-2x+36y+253=0 | | -5x^2+47x-56=0 | | 0.400x+3-0.800x=.200 | | 6x-3(6x-7)=-75 | | x=20-4x | | 2z^2+19Z+42= | | x+(x+1)+(x+2)=72 | | ((20x)+(x)).5=14x | | 4x^3-12x+8=0 | | 5x+7(-2x+9)=18 | | x=20-4xs | | 4+9x=81 | | x^3+8=10x-x^2 | | 6z^2-5=13z | | 5x^2+20x=-5x^2+3x-6 | | -2y^2+32y-128=0 | | 5y^2+43y+24= | | ((3x-1)+(7x+1)).5=10 | | 6x^2+16x=-x+3 | | 5x-4(-x+4)=92 | | 0.500x+1+0.750x=-9 | | 9m.-28=2m | | 30-2m=6(1-3m)-8m | | x+3x=16 | | 3x-6(x-3)=54 | | -9y-4+10y+7=11 | | 7(x-4)+3(x+5)=47 | | 3x^3+2x-8=0 | | X+3+2x-8=28 | | 0.625m-0.600+0.375m=0.400 | | 4+(3-2x)+5=18 |